(untitled) (Politeja, 2019)
The author claims that contemporary cooperation between the state and a citizen in Russia is evolving from a state-centralist model to a kind of partnership. The degree and quality of the state’s cooperation is determined by the hybrid nature of the Russian political system – a combination of elements of democratic institutions and autocratic methods of governance. Cooperation between the state and a citizen should be discussed in the context of attaining the opportunities for cooperation between the citizens and the state in order to achieve general aims, as a means of resolving problems. The author holds the opinion that cooperation can be not only an expression of solidarity, but also a testament to peaceful coexistence (not aimed at wrangling). What serves as an indicator of such cooperation between the state and a citizen is trust in the authorities. It should be said that in the conditions of unconsolidated democratic culture of cooperation between the state and the society, the attitude of the majority of citizens to the contemporary political authorities in Russia is, to a high degree, based on trust in Vladimir Putin. However, the noticeable decrease in the level of trust to certain institutions of authority is a result of the inaction, immorality, and corruption of certain groups of policymakers or representatives of the authorities. One of the major challenges of the authorities is how to increase social trust in political institutions.